Conformational Dynamics of apo‐GlnBP Revealed by Experimental and Computational Analysis. (12th October 2016) - Feng, Yitao; Zhang, Lu; Wu, Shaowen; Liu, Zhijun; Gao, Xin; Zhang, Xu; Liu, Maili; Liu, Jianwei; Huang, Xuhui; Wang, Wenning
Abstract: The glutamine binding protein (GlnBP) bindsl ‐glutamine and cooperates with its cognate transporters during glutamine uptake. Crystal structure analysis has revealed an open and a closed conformation for apo‐ and holo‐GlnBP, respectively. However, the detailed conformational dynamics have remained unclear. Herein, we combined NMR spectroscopy, MD simulations, and single‐molecule FRET techniques to decipher the conformational dynamics of apo‐GlnBP. The NMR residual dipolar couplings of apo‐GlnBP were in good agreement with a MD‐derived structure ensemble consisting of four metastable states. The open and closed conformations are the two major states. This four‐state model was further validated by smFRET experiments and suggests the conformational selection mechanism in ligand recognition of GlnBP.